Heat flow measurements in Lutzow-Holm Bay, Antarctica - Nagao, Toshiyasu; Kaminuma, Katsutada (1983)
P(論文) Five heat flow measurements were made during the winter season of the 22nd Japanese Antarctic Research Expedition in the Lutzow-Holm Bay, Antarctica. The apparatus used for the temperature measurements was a 1.2m long Bullard type probe with three thermistors. Temperature gradients were determined at five different sites in shallow waters on the shore fast sea ice in November 1981. The temperature data were corrected following Bullard's method. The temperature gradients ranged from -0.028 to 0.197℃/m. The thermal conductivities were determined on sediment samples recovered by coring before the temperature measurements were made. The thermal conductivities ranged 2.25 to 2.63×(10)^<-3>cal/cm・s℃. Corrected heat flow values were -0.74,0.21,4.39,4.53 and 1.19 HFU. Since these measurements were made in shallow water, the effects of the sea floor topography and the water temperature variation were considered. The topographic effect computed by a two-dimensional relaxation method resulted in corrections ranging from 7 to 41%. Annual sinusoidal temperature variation with an assumed amplitude of 0.31℃ at the sea floor gave a correction of up to ±4.2 HFU. Because of the sea floor temperature in November is increasing, the temperature gradient of sediments has a tendency to decrease. Therefore, the high heat flows valued 4.39 and 4.53 HFU can not be denied. departmental bulletin paper